Clinical and Genetic Analysis of a Patient with CMT4J - Leema Reddy Peddareddygari; Raji P. Grewal (MDPI AG, 2022)
We report the clinical and genetic analysis of a patient with a rare form of an autosomal recessive genetic neuropathy, Charcot Marie Tooth (CMT) disease type 4J. She presented at age 62 years with signs and symptoms consistent with a mild neuropathy. The onset of symptoms began approximately ten years earlier. Electrophysiological testing confirmed a demyelinating neuropathy and a comprehensive neuropathy screening for common causes of neuropathy was unrevealing. She underwent commercial whole exome sequencing, analyzing more than eighty genes known to cause neuropathy. Two mutations were detected, c.122T > C, p.Ile41Thr and c.2247dupC, p.Ser750GlnX10 in the FIG4 gene. The p.Ile41Thr mutation, which is paternally inherited, is a recurrent mutation reported in a number of unrelated families of European descent. The patient's father, also of European descent, provides further evidence supporting a founder effect for this mutation. In most patients carrying the p.Ile41Thr mutation, the neuropathy, unlike our patient, is often severe with early onset. The second mutation, c.2247dupC, p.Ser750GlnX10 is maternally inherited and not previously reported. Furthermore, based upon our protein modeling analysis, c.2247dupC is disease producing, representing a novel pathogenic mutation. Our study of this patient expands the clinical and genetic spectrum of patients with CMT 4J.